Stock assessment of silverbellies of India with particular reference to Andhra Pradesh and Tamil Nadu - Murty, V Sriramachandra; Srinath, M; Livingston, P; Sastri, Y Appanna; Srinivasarengan, S (Indian Journal of Fisheries, 2011)
Along Indian coasts, the silveifoellies are exploited by trawl and aitisanal gears but bulk of the landingsare obtained by tiawlt which operate up to SO m depth. During 1979-83, the estimated annual averagesilvetbelly landings were 69 000 tonnes, whereas during 1984-88 these were 62 000 tonnes. Maximumsilveibelly landings were obtained in Tamil Nadu which contributed 70.5% ol total all-India silverbellylandings followed by Andhra Pradesh (9%), Kerala (8.4%), Kamataka (6%) and other sutes (6.1%). Outof 20 species of silveibellies, known to occur in the seas around India, LeiogiuUhus bindus and Secutorinsidiator were most dominant along Andhra Pradesh and northern Tamil Nadu coasts, together contributingto 64% and SS% respectively of tilveibeUy landings. Along southern Tamil Nadu, L. joiusi and L.dussumeri were most dominant together forming about 60% of silvetbelly catch in the region.